PENGARUH DAYA TARIK IKLAN DAN BRAND TRUST TERHADAP MINAT PENGGUNA JASA TRANSPORTASI ONLINE MAXIM - Rini Oktavia; Sri Ekowati (UM. Bengkulu, 2023)
User interest is the desire of consumers to use a product or service. Several factors that influence user interest include advertising attractiveness and brand trust. This study aims to determine the effect of advertising attractiveness and brand trust on user interest in Maxim online transportation services. This type of research is quantitative research with a descriptive approach. The object of this study were all students of the Management Study Program class of 2019. The number of research samples was 65 people. Data collection was carried out using a questionnaire. The data analysis technique uses multiple linear regression analysis techniques. The results showed that partially the attractiveness of advertising has a positive and significant effect on user interest in Maxim online transportation services and brand trust has a positive and significant effect on user interest in Maxim online transportation services. Simultaneously, there is an influence of advertising attractiveness and brand trust on user interest in Maxim online transportation services. Keywords: User Interest, Advertising, Brand Trust